9 Staff training and test running of new obstetrics service using different simulation modalities. (17th November 2016) - Farooq, Omer; Sallis, S; Chambers, J; Purva, M
Abstract : Introduction: Simulation is an effective training tool that helps to improve knowledge and skills. 1 Use of in situ simulation (ISS) I-e simulation in workplace contributes to evaluation of new services. 2 We utilised simulation to educate staff and evaluate a new enhanced recovery pathway for elective caesarean section that meant immediate post caesarean section, patient care would be carried out at site removed from the labour ward, where it was previously taking place. Methods: Eleven midwives attended drill sessions lasting for 2 hours in groups of 2 to 6. Key areas of training were airway management, post-operative bleeding, local anaesthetic toxicity and high spinal block. Six midwives and coordinator attended ISS. Simulated patient and Simpad for live monitoring were used. Scenario involved post caesarean section patient with airway compromise and bleeding. Immediate debriefing followed by recommendations to parent department in view of the suggestions by participants were reported to parent department. Results: Improvement in confidence in dealing with postoperative emergencies from 2.8 to 4.3 out of 5, was reported by staff post simulation. ISS highlighted lack of awareness about location of emergency equipment and reluctance to use resuscitation trolley in emergency scenarios. Staff raised concerns regarding availability of staff members for "group hug" and dealing with unexpected delay in discharge. It was also highlighted that proper labelling of drugs in emergency trolleys and repair of broken keys box were required immediately. Conclusions: Use of a hybrid simulation model in an insitu setting helped us deliver good quality training and effective evaluation of a new patient pathway. Staffs involved in ISS were thankful to faculty as the session provided them with the opportunity to look at new pathway in action that in turn alleviated many of their concerns. We highly recommend use of hybrid simulation for training and system evaluation. References: Schmidt E, Goldhaber-Fiebert SN, Ho LA, et al . Simulation exercises as a patient safety strategy: a systematic review. Ann Intern Med 2013;158 (5 Pt 2):426–32. doi:10.7326/0003-4819-158-5-201303051-00010 Ventre KM, Barry JS, Davis D, et al . Using In Situ simulation to evaluate operational readiness of a children's hospital-based obstetrics unit. Simul Healthc 2014;9 (2):102–111. doi:10.1097/SIH.0000000000000005